Mental health and sleep correlates of self-reported outdoor daylight exposure in over 13,000 adults with depression - Jacob J. Crouse; Shin Ho Park; Brittany L. Mitchell; Enda M. Byrne; Sarah E. Medland; Tian Lin; Jan Scott; Zsofi de Haan; Emiliana Tonini; Frank Iorfino; Naomi R. Wray; Nicholas G. Martin; et al. (European Psychiatry)
Abstract